2019
DOI: 10.5603/cj.a2018.0029
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of zero or near zero fluoroscopy during catheter ablation procedures

Abstract: Background: Awareness of risks associated with radiation exposure to patients and medical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…As expected, there was a significant reduction in both fluoroscopy duration and DAP using an LF approach, however, we also found that overall procedure time was also lower in the LF arm than the CF arm, which suggests that reliance on fluoroscopic imaging during PVI for confirmation of catheter position and sheath manipulation may not only be unnecessary, but also less efficient. Of the 15 studies included in this meta‐analysis, two studies were able to safely accomplish acute PVI in the LF arm without the use of any procedural fluoroscopy, 10,14 and five other studies were able to accomplish PVI in the LF arm with near‐zero fluoroscopy levels 7,8,15,19,20 . In one study, acute isolation was achieved successfully by ICE‐guidance in the LF arm without 3D mapping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, there was a significant reduction in both fluoroscopy duration and DAP using an LF approach, however, we also found that overall procedure time was also lower in the LF arm than the CF arm, which suggests that reliance on fluoroscopic imaging during PVI for confirmation of catheter position and sheath manipulation may not only be unnecessary, but also less efficient. Of the 15 studies included in this meta‐analysis, two studies were able to safely accomplish acute PVI in the LF arm without the use of any procedural fluoroscopy, 10,14 and five other studies were able to accomplish PVI in the LF arm with near‐zero fluoroscopy levels 7,8,15,19,20 . In one study, acute isolation was achieved successfully by ICE‐guidance in the LF arm without 3D mapping.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, current practice guidelines recommend minimizing fluoroscopy usage during AF ablation procedures to as low as reasonably achievable in the EP laboratory to limit radiation dose exposure 1,6 . Recently, numerous observational and randomized studies have explored the feasibility and safety of low and zero fluoroscopic radiofrequency (RF) approaches for PVI in comparison to conventional approaches, although all are single‐center studies and the majority have been observational 7‐21 . To better understand the generalizability of low fluoroscopy (LF) approaches for PVI for AF in clinical practice we conducted a meta‐analysis to derive comprehensive estimates of clinical efficacy, safety and procedural parameters between studies comparing low/zero fluoroscopy to conventional fluoroscopy (CF) approaches for PVI.…”
Section: Introductionmentioning
confidence: 99%
“…Small case series evaluating fluoroless approaches for the ablation of paroxysmal AF have also been reported. 17,[49][50][51][52] In 245 patients with paroxysmal AF, Lyan et al 50 Different from other patient series, O'Brien et al 53 reported their experience with a fluoroless approach using three-dimensional EAM and TEE rather than ICE in a total of 55 AF patients. The total procedural time was similar to that in the fluoroscopic approach group used as a control population and was consistent with previous series performed using ICE instead of TEE.…”
Section: State Of Fluoroless Procedures For Atrial Fibrillationmentioning
confidence: 99%
“…to zero under increasing experience of 3D mappings systems and intracardiac electrocardiography. 33,34…”
Section: Advances In Atrial Fibrillation Ablation Devicesmentioning
confidence: 99%